Synthesis of Magnetite/Chitin/Fulvic Acid Derived from Goat Manure Compost and Adsorption Study of Zn(II) for Water Security Enhancement - Aisyah, Audrey Nur; Sandri, Azzahra; Hutama, Raihansyah Raja; Kuntjahjono, Mayang Fauziah Putri; Napoleon, Sultan; Basuki, Rahmat (Indonesian Scholar Society, 2025)
Water pollution due to heavy metals such as Zn(II) poses a risk to the environment and health. This study aims to synthesize Magnetite/Chitin/Fulvic Acid (AF)-based composite adsorbent from goat feces compost and evaluate its effectiveness in adsorbing Zn(II) ions. Fulvic acid was extracted through alkaline-acid method and synthesized together with chitin and magnetite using one pot coprecipitation method. Characterization using FTIR, XRD, and BET showed successful synthesis with mesoporous structure for BET (average pore size 6.15 nm, surface area 41.77 m²/g). Isotherm studies showed that the adsorption of Zn(II) showed a good fit with the Freundlich (R² = 0.9967) and Temkin (R² = 0.9968) models, indicating multilayer adsorption on the heterogeneous surface. The composite also shows good adsorption ability and can be magnetically separated, making it an environmentally friendly and efficient potential adsorbent for wastewater treatment applications.